2021
DOI: 10.1186/s12974-021-02071-9
|View full text |Cite
|
Sign up to set email alerts
|

Activated STAT3 signaling pathway by ligature-induced periodontitis could contribute to neuroinflammation and cognitive impairment in rats

Abstract: Background Increasing evidence suggests a causal link between periodontitis and cognitive disorders. Systemic inflammation initiated by periodontitis may mediate the development of cognitive impairment. Our study aims to investigate the effect of ligature-induced periodontitis on cognitive function and the role of signal transducers and activators of transcription 3 (STAT3) in this process. Materials and methods Ligature-induced periodontitis was e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 44 publications
2
52
0
Order By: Relevance
“…GFAP, a class III intermediate filament, is a cell-specific marker that distinguishes astrocytes from other glial cells during the development of the central nervous system. A rabbit polyclonal GFAP antibody from Abcam (Abcam Cat# ab7260, RRID: AB_2893014) was used in the present study because this antibody has been demonstrated to specifically react with GFAP in rats and mice (Hu et al, 2021;Sinha et al, 2021). The immunizing antigen of the antibody is the recombinant full-length protein corresponding to human GFAP.…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…GFAP, a class III intermediate filament, is a cell-specific marker that distinguishes astrocytes from other glial cells during the development of the central nervous system. A rabbit polyclonal GFAP antibody from Abcam (Abcam Cat# ab7260, RRID: AB_2893014) was used in the present study because this antibody has been demonstrated to specifically react with GFAP in rats and mice (Hu et al, 2021;Sinha et al, 2021). The immunizing antigen of the antibody is the recombinant full-length protein corresponding to human GFAP.…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…The phosphorylation and activation of STAT3 influences the transcription of HIF1A , which affects hypoxia-mediated cell damage [ 18 , 19 ]. When the inflammatory response was intensified, the JAK2-STAT3 pathway was activated in HMC3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 (signal transducer and activator of transcription 3) activation is implicated in inflammation-associated carcinogenesis, and its phosphorylation by H. pylori has been documented [ 61 ]. STAT3 pathway activation is documented in periodontitis [ 62 ] and is also found to contribute to neuroinflammation [ 63 ]. EZH2 encodes for a methyltransferase enzyme that is involved in osteoclast regulation and is proposed as a target for periodontitis [ 64 ].…”
Section: Discussionmentioning
confidence: 99%